2005
DOI: 10.1111/j.1365-2133.2005.06530.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a chemoattractive proinflammatory cytokine response after stimulation of keratinocytes with Propionibacterium acnes and coproporphyrin III

Abstract: This cytokine pattern may favour a chemotactic response and implicates P. acnes and coproporphyrin III in the recruitment of inflammatory cells to the site of infection and in the development of acne lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 19 publications
4
71
0
3
Order By: Relevance
“…Furthermore the recovery time of 3 h was not sufficient to track a complete restoration to baseline values. The effect of skin pH on the growth of Proprionibacterium acnes [25, 26], the induction of an inflammatory process [27] and the negative impact of oleic acid in the pilosebaceus glands on the growth of P. acnes [28] are known. Regular sauna seems to decrease one of the basic requirements for the development and aggravation of acne [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the recovery time of 3 h was not sufficient to track a complete restoration to baseline values. The effect of skin pH on the growth of Proprionibacterium acnes [25, 26], the induction of an inflammatory process [27] and the negative impact of oleic acid in the pilosebaceus glands on the growth of P. acnes [28] are known. Regular sauna seems to decrease one of the basic requirements for the development and aggravation of acne [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a secreted peptidoglycan of P. acnes stimulates the production of proinflammatory cytokines, such as IL-1, IL-8, and TNF-, by human monocytic cell lines and freshly isolated peripheral blood mononuclear cells from acne patients. [19][20][21][22] In a recently published study, heatkilled P. acnes stimulated THP-1 cells to produce IL-8 and TNF-. 23) Hence, to determine the anti-inflammatory effects of Geumgamja and Cheonyahagyul, we measured IL-8 and TNF-concentrations in THP-1 cells by ELISA.…”
mentioning
confidence: 99%
“…30,31 Recently, it has also been described that P. acnes triggers anti-microbial peptide and cytokine secretion of keratinocytes in vitro. [23][24][25] P. acnes, itself, is able to induce cytokines-like such as TNFa, IL-1a and IL-8. 26,27 Moreover the genome sequence of P. acnes is known to encode many factors that may have inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] In this context, we hypothesized that P. acnes is able to increase CRH expression by keratinocytes, representing a local stress in acne. We thus evaluated the modulation of CRH also described.…”
Section: Introductionmentioning
confidence: 99%